2022
DOI: 10.7150/thno.73235
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC-mediated mutagenesis is a favorable predictor of prognosis and immunotherapy for bladder cancer patients: evidence from pan-cancer analysis and multiple databases

Abstract: Background: The APOBEC (apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like) family-mediated mutagenesis is widespread in human cancers. However, our knowledge of the biological feature and clinical relevance of APOBECs and APOBEC mutagenesis in cancers remains limited. Methods: In this study, with a series of bioinformatic and statistical approaches, we performed a comprehensive analysis of multiple levels of data, including whole-exome sequencing (WES) and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…Therefore, screening novel biomarkers to help develop patient-specific therapies and improve prognosis remains critical and urgent. Distinct from bulk RNA-seq focusing on the average expression level of genes in cells, scRNA-seq has emerged as a useful tool for transcriptional stratification to define the cell subpopulations and realize specific biomarkers and heterogeneity among different cell types in various cancers, including BLCA [ 28 ]. Therefore, in this study, we conducted a comprehensive analysis of bulk RNA-seq and scRNA-seq to develop a risk model that exhibited excellent prognostic and predictive efficacy for immunotherapy response in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, screening novel biomarkers to help develop patient-specific therapies and improve prognosis remains critical and urgent. Distinct from bulk RNA-seq focusing on the average expression level of genes in cells, scRNA-seq has emerged as a useful tool for transcriptional stratification to define the cell subpopulations and realize specific biomarkers and heterogeneity among different cell types in various cancers, including BLCA [ 28 ]. Therefore, in this study, we conducted a comprehensive analysis of bulk RNA-seq and scRNA-seq to develop a risk model that exhibited excellent prognostic and predictive efficacy for immunotherapy response in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PD 1 or PD L1 monoclonal blocking antibodies are applied on PD L1-positive tumors to correct the immunosuppression of T cells in TME (Lei et al, 2020). Researchers are also exploring the relevance of gene mutations to immune in ltration (Shi et al, 2022). Our results showed that ZWINT expression was negatively correlated with the in ltration values of T cell CD4 + central memory, T cell CD4 + effector cells and tumor-associated broblasts, and positively correlated with the in ltration values of T cell CD4 + Th2 cells and MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer T-reg, Th2, and TAM cells Mouse [ 164 ] 3B Activating More tumor-infiltrating lymphocytes Patient [ 165 ] 3B Activating Immune activation in pan-cancer analysis Patient [ 162 ] 3C-H Activating More CD8+ T-cells with greater receptor diversity and cytolytic activity Patient [ 48 ] Bladder 3B Activating Enrichment of immune-related signatures, including IFN-γ Patient [ 46 ] Mutation burden Activating Higher neoantigen loads, activated CD4+ T cells, CD8+ T cells, and M1 cells. Fewer MDSCs and naïve CD4+ T cells Patient [ 160 ] 3B Activating More cytotoxic T-cells with a higher CD8+/CD3+ ratio Patient [ 35 ] Glioma 3B, 3C, 3D, 3F, 3G, 3H Activating Increased myeloid cell infiltration, IFN-γ signaling, and PD-L1/2 expression Patient [ 51 ] Lung 3B Activating More activated CD4+ T cells, CD8+ T cells, and NK cells. Fewer regulatory T cells Patient [ …”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%